Nilai-nilai Pendidikan Karakter Tokoh Kresna dalam Pertunjukkan Wayang Kulit Lakon Kresna Duta Ki Sigit Manggolo Seputro - Satoto, Angga Bimo; Widayat, Afendy; Hapsari, Diah Retno (Mudra Jurnal Seni Budaya, 2024)
Current era of information and technology openness does not always have a positive impact on humans but there are also negative impacts, one of which is the moral decline in society, especially children and adolescents. One way to improve the morale of the nation's children is by reintroducing traditional arts which contain a lot of character education values in them, one of which is the wayang kulit performance. This study explores the values of character education in the character Kresna in the story Kresna Duta presented by Ki Sigit Manggolo Seputro. The data in this study were sourced from the transcription of the wayang kulit performance Kresna Duta by Ki Sigit Manggolo Seputro. The analysis technique used in this research is data analysis technique the Miles and Hubernam model.The results of this study reveal that there are 13 values of character education based on the perspective of the Ministry of Education of the Republic of Indonesia that exist in the figure of Kresna namely: 1) religious, 2) democratic, 3) friendly, 4) hard work, 5) honest, 6) independent, 7) love the motherland, 8) creative, 9) love peace, 10) responsibility, 11) appreciate achievement, 12) social care and 13) tolerance. Wayang kulit performance lakon Kresna Duta by Ki Sigit Manggolo Seputro can be a good alternative solution to increase the morale of the nation's youth, one of which is through the teachings of character education values.